Generation of human monoclonal antibodies: the development of methods to identify and isolate neutralising antibodies targeted to Ebolavirus from peripheral blood - Bailey, Graham D. (2017)
Neutralising antibodies are an essential component in the immune response to virus infection and are often effective at preventing or attenuating viral diseases. The administration of cocktails of potently neutralising monoclonal antibodies (nAb) to abrogate viral infections has been demonstrated as an effective treatment to control disease progression caused by a diverse range of viruses. The mechanism of neutralisation is mediated predominantly by nAb binding to glycosylated envelope proteins displayed on the surface of virus particles, thereby preventing binding to host cell membrane bound receptor proteins and neutralising the entry process. Although a robust nAb response is elicited following infection with a number of viruses, many human viruses have evolved mechanisms to effectively evade the humoral immune response. The emergence or re-emergence of pathogenic human viruses poses a significant threat to the global population. The Ebolavirus epidemic of 2014-2015 arose from the emergence of a known virus in a new area, which rapidly spread through a naïve population with devastating consequences, resulting in 11,323 fatalities from a total of 28,646 confirmed cases of infection. A rapid induction of potent, broadly nAbs was a possible pathway for infection control in the 17,323 survivors of the epidemic. The isolation of potent nAbs from seroconverted individuals following antigenic exposure provides the potential to develop novel therapeutics for administration within a region affected by an epidemic. To this end, the aim of this project was to develop a platform of methods to isolate human monoclonal antibodies directly from peripheral blood through the isolation of memory B-lymphocytes and subsequent stimulation to secrete antibodies using an in vitro culture system. Identification of DNA sequences encoding antibody heavy and light chain variable domains (VH and VL respectively), allowed for the production of recombinant antibody following the sub-cloning of VH and VL regions into plasmid expression vectors to provide a proof of principle of platform function. Secondly, the introduction of functional screens to the platform would provide a method to identify antibodies derived from memory B-cells with the ability to neutralise Ebolavirus pseudo-particles using in vitro entry inhibition assays.